The use of PhaseNet and GaMMA in microseismic monitoring in geothermal fields - Ambara Putra, I Putu Raditya (Jurnal Ilmiah MTG, 2023)
Due to its potential to decrease greenhouse gas emissions and decrease dependence on fossil fuels, geothermal energy has recently attracted more attention as a renewable and sustainable form of power generation. For evaluating the reservoir's integrity and understanding the underlying geomechanical processes in geothermal fields, microseismic monitoring is crucial. To accurately analyze and understand these microseismic occurrences, it is necessary to accurately identify their phases. Therefore, in this study, we used the PhaseNet-GaMMA combination to identify the arrival times of P and S and associate them to determine the microseismic events of these phases. PhaseNet-GaMMA succeeded in detecting a greater number of phases and events compared to catalog data, where the identification match rate was 85%. Even so, the time required for automatic detection of PhaseNet-GaMMA is relatively short and simple, so it is very good if used as an initial stage in the process of identifying phases and microevents in geothermal fields.